(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Good nutrition requires a satisfactory diet, which is capable of supporting the individual consuming it; it is a state of good health by providing the desired nutrients in required amounts. It must provide the right amount to fuel to execute normal physical activity. If the total nutrients provided in the diet is insufficient, a state of under nutrition will develop. Methods: A quantitative non experimental research approach was adopted for this study. The samples were selected using purposive sampling technique. The sample considered of 112 mothers of under-five children. The instruments used for data collection were demographic characteristics and a structured knowledge questionnaire. Results: The overall grading of knowledge score showed that one-third of the subjects 63 (55.3%) had adequate knowledge and 49 (44.5%) of the subjects had inadequate knowledge regarding child nutrition. Conclusion: The overall findings of the study clearly showed that mothers had adequate knowledge regarding child nutrition.